Thermochemical Properties of Glass Wool/Maerogel Composites - Bahador Dastorian Jamnani; Soraya Hosseini; Amin Shavandi; Mohd Roshdi Hassan (Advances in Materials Science and Engineering, 2016)
Aerogel blankets are composites of silica aerogel particles dispersed in a reinforcing fiber matrix that turns the brittle aerogel into durable and flexible insulating materials. In this study, silica aerogel was loaded on glass wool with different concentrations (0–18.6%) and morphological and thermal characteristics of the aerogel blankets were studied. Rate of modified blanket decomposition was slower at temperatures between 250°C and 650°C due to the retardant effect of the silica aerogel. The average diameter of the fiber for either original glass wool or modified glass wool materials was approximately 20 μm and samples had porous, interconnected particles with dendritic-like structure.